BPM and ECM: Similarities, differences, conceptual, and technological limits - Mendes, Marco Aurélio de Souza; Bax, Marcello Peixoto; Bax, Marcello Peixoto; Bax, Marcello Peixoto; Bax, Marcello Peixoto (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
Enterprise information architectures still do not deliver all the value that comes from integrating structured and unstructured information. Enterprise Content Management and Business Process Management were developed as autonomous disciplines. Thus, Enterprise Content Management still occurs without formally considering the business processes that generate and manipulate content, while Business Process Management initiatives arise without a documented treatment of materials produced by the processes. The non-integrated approach to these disciplines collaborates to reduce the potential benefits expected in Organizational Change Management programs. In such context, the article discusses the interrelation between Business Process Management and Enterprise Content Management, approaching from a historical view of these disciplines, their conceptual limits, technological support, and dialogues that would benefit both initiatives. The paper contributes to clarify a question still vague in the field of Information Management, which is how to integrate Business Process Management and Enterprise Content Management treating structured and unstructured information in a unified manner. It discusses how to approach this issue in a broad scope of IM by combining the concepts of Enterprise Content Management and Business Process Management. Based on a literature review, the paper analyzes and synthesizes experiences in Enterprise Content Management and Business Process Management acquired in the context of a project carried out in a Power Sector Company. The article reveals problems in separating approaches to Enterprise Content Management and Business Process Management. It shows the importance of an effort for integration and presents three instruments that promote the linkage of the two initiatives, approximating process offices and analysts’ information. Keywords: Archival sciences. Business process management. Document management. Enterprise content management. Link: http://www.scielo.br/pdf/tinf/v30n1/2318-0889-tinf-30-1-0095.pdf